Acute renal failure after rifampicin - Adriana Weinberg; A. Barone; Luis B. Saldanha; Mario Shiroma (Revista do Instituto de Medicina Tropical de São Paulo, 1984)
A patient with miliary tuberculosis and a chronic urogenital focus is described, who had a borderline renal function at diagnosis and developed overt renal failure upon daily treatment with rifampin (RMP), isoniazid (INH) and ethambutol (EMB). This is the first Brazilian report of BMP induced renal damage. A renal biopsy taken on the third day of oliguria showed recent tubular necrosis with acute interstitial inflammation and granuloma formation. The aspect of the granulomatous lesion hightly suggested drug etiology because of the lack of palisading, high incidence of neutrophils and absence of facid-fast bacilli. This is the first presentation of an acute granulomatous interstitial nephritis probably due to RMP. Furthermore the pathogenesis of the renal damage caused by tuberculosis and RMP are discussed.